2021
DOI: 10.2217/fon-2020-0969
|View full text |Cite
|
Sign up to set email alerts
|

KEYNOTE-975 Study Design: a Phase III Study of Definitive Chemoradiotherapy Plus Pembrolizumab in Patients with Esophageal Carcinoma

Abstract: Despite curative-intent treatment, most patients with locally advanced esophageal cancer will experience disease recurrence or locoregional progression, highlighting the need for new therapies. Current guidelines recommend definitive chemoradiotherapy in patients ineligible for surgical resection, but survival outcomes are poor. Pembrolizumab is well tolerated and provides promising antitumor activity in patients with previously treated, advanced, unresectable esophageal/esophagogastric junction cancer. Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Additionally, an ongoing phase Ib-2 trial (CP-MGAH22-05) also revealed that margatuximab in combination with pembrolizumab had good tolerability and efficacy in the treatment of human epidermal growth factor receptor 2 (HER2) positive gastroesophageal adenocarcinoma (33). KEYNOTE-975, a randomized, multicenter, double-blind, phase III study investigating the possibility of using pembrolizumab in the definitive chemoradiation setting, is currently in the patient recruitment stage (34). Patients with inoperable locally advanced, but non-metastatic ESCC or adenocarcinoma or Siewert type 1 adenocarcinoma of the EGJ will be randomly assigned (1:1) to receive pembrolizumab plus definitive chemoradiotherapy (dCRT) or a placebo plus dCRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, an ongoing phase Ib-2 trial (CP-MGAH22-05) also revealed that margatuximab in combination with pembrolizumab had good tolerability and efficacy in the treatment of human epidermal growth factor receptor 2 (HER2) positive gastroesophageal adenocarcinoma (33). KEYNOTE-975, a randomized, multicenter, double-blind, phase III study investigating the possibility of using pembrolizumab in the definitive chemoradiation setting, is currently in the patient recruitment stage (34). Patients with inoperable locally advanced, but non-metastatic ESCC or adenocarcinoma or Siewert type 1 adenocarcinoma of the EGJ will be randomly assigned (1:1) to receive pembrolizumab plus definitive chemoradiotherapy (dCRT) or a placebo plus dCRT.…”
Section: Discussionmentioning
confidence: 99%
“…The trial will attempt to determine whether pembrolizumab combined with dCRT can prolong OS and improve tolerability in patients with advanced EC compared to dCRT alone. The trial has not distinguished between different PD-L1 expression status during patient enrolment, and again, PD-L1 positivity has been defined as a CPS of ≥10 (34). Other ongoing clinical trials including NCT02844075, NCT02998268, NCT03322267, NCT04389177, and NCT04435197 are expected to yield further clinical evidence to illustrate the efficacy and tolerability of pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to further improve the survival of these patients, several trials addressing this issue are currently ongoing. The KEYNOTE-975 trial aims to investigate the benefit of the combination of definitive chemoradiotherapy plus pembrolizumab in patients with esophageal carcinoma [ 25 ]. Furthermore, the SKYSCRAPER-07 trial evaluates the efficacy and safety of tiragolumab, a monoclonal antibody designed to bind with TIGIT (a protein receptor on immune cells), plus atezolizumab, a humanized monoclonal antibody immune checkpoint inhibitor that selectively binds to PD-L1, compared with the placebo in participants with localized but unresectable esophageal SCC following definitive concurrent chemoradiotherapy.…”
Section: Esophageal Cancer In Localized Settingmentioning
confidence: 99%
“…These drugs are usually given in combinations to improve their efficacies. Furthermore, to limit off-target, increase optimal therapeutic effects, and improve survival outcomes, chemotherapeutic agents are now administrated with some molecular target drugs such as trastuzumab, nivolumab, pembrolizumab, ramucirumab, fam-trastuzumab deruxtecan-nxki, and cetuximab [12,14,15]. Early-stage cancer treated with chemotherapy has shown improved survival rates, particularly in combination with radiation, while a poor prognosis is observed in advanced-stage esophageal cancer [15,16].…”
Section: Classic Treatment Of Esophageal Cancermentioning
confidence: 99%